2020
DOI: 10.1021/acs.jafc.0c00316
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Commercially Important Carotenoids (Lycopene, β-Carotene, and Astaxanthin) by Natural Catalysts: Isothiocyanates and Polysulfides

Abstract: Effects of natural catalysts, isothiocyanates and polysulfides, on Z-isomerization and decomposition of (all-E)carotenoids (lycopene, β-carotene, and astaxanthin) after heat treatment were investigated. When isothiocyanates were added to (all-E)-carotenoid solutions and heated, Z-isomerization and decomposition of carotenoids were enhanced and the degree differed depending on the isothiocyanate type. Interestingly, when polysulfides were applied in the same manner, in addition to promoting the Z-isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 59 publications
0
97
0
Order By: Relevance
“…[ 23,24 ] Furthermore, these studies clearly indicated that the speed of E / Z ‐isomerization and the type of isomers generated during storage differed depending on the kind of carotenoid. [ 9,20–25 ] For example, when ethyl acetate solutions of all‐ E ‐isomers of lycopene, β‐carotene, and astaxanthin were heated at 60 °C for 1 h, the total Z ‐isomerization contents increased in the following order: β‐carotene (23.3%) > lycopene (20.5%) > astaxanthin (5.9%). [ 25 ] Moreover, Murakami et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23,24 ] Furthermore, these studies clearly indicated that the speed of E / Z ‐isomerization and the type of isomers generated during storage differed depending on the kind of carotenoid. [ 9,20–25 ] For example, when ethyl acetate solutions of all‐ E ‐isomers of lycopene, β‐carotene, and astaxanthin were heated at 60 °C for 1 h, the total Z ‐isomerization contents increased in the following order: β‐carotene (23.3%) > lycopene (20.5%) > astaxanthin (5.9%). [ 25 ] Moreover, Murakami et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9,20–25 ] For example, when ethyl acetate solutions of all‐ E ‐isomers of lycopene, β‐carotene, and astaxanthin were heated at 60 °C for 1 h, the total Z ‐isomerization contents increased in the following order: β‐carotene (23.3%) > lycopene (20.5%) > astaxanthin (5.9%). [ 25 ] Moreover, Murakami et al. [ 22 ] reported that photo‐irradiation promoted all‐ E ‐isomerization of lycopene, whereas Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…n.d., Not detected substantially. b Tentatively assigned in the literatures 9,25,26,[29][30][31][32][33][34][35] .…”
Section: Synergistic Effects Of Food Ingredients and Vegetable Oils Omentioning
confidence: 99%
“…Mustard oil contains a large quantity of isothiocyanates, especially allyl isothiocyanate 41 . Isothiocyanates have a strong carotenoid isomerization-promoting effect 29,42 , and thus the use of mustard oil would enhance the thermal Z-isomerization reaction. In fact, we analyzed the volatile components of olive, sesame, and mustard oils used in this study by gas chromatography/ electron ionization-mass spectrometry GC/EI-MS; Agilent-7890A GC instrument coupled with 5975 MSD; Agilent Technologies Inc., Palo Alto, CA, USA , and confirmed that olive oil contained no polysulfides and isothiocyanates but sesame and mustard oils contained dimethyl disulfide and allyl isothiocyanate, respectively 43 .…”
Section: Effect Of the Combined Use Of Food Ingredients And Vegetablementioning
confidence: 99%
See 1 more Smart Citation